No periodic orbits for the type A Bianchi's systems - Buzzi, Claudio A. [UNESP]; Llibre, Jaume (Taylor & Francis Ltd, 2015)
It is known that the 6 models of Bianchi class A have no periodic solutions. In this article we provide a new, direct, unified and easier proof of this result.
Keywords: Bianchi cosmological models; Periodic orbits